DOI: 10.31274/etd-180810-180
|View full text |Cite
|
Sign up to set email alerts
|

Variation of carnitine concentrations in Angus beef

Abstract: The objective of this study was to quantify the naturally occurring L‐carnitine, acylated carntine, and total carnitine in Angus beef. Our ultimate goal is to optimize the genotype of an animal to select beef cattle with high carnitine concentration. Discovery samples were collected from 1,056 purebred Angus bulls, steers, and heifers beef from different parts of the US. These samples were used to quantify forms of carnitine in beef. Additionally, about 1,000 validation samples were collected to validate disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 93 publications
0
4
2
Order By: Relevance
“…Furthermore, the carnitine content of plasma and of the heart and skeletal muscles was higher in male than in female rats . In addition, it was reported that the carnitine content increased with the age of the animal . Hence the contradictory result found in this study compared with previous experiments regarding the effect of sex on carnitine content of meat is likely be due to the differences in age of the animals.…”
Section: Resultscontrasting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, the carnitine content of plasma and of the heart and skeletal muscles was higher in male than in female rats . In addition, it was reported that the carnitine content increased with the age of the animal . Hence the contradictory result found in this study compared with previous experiments regarding the effect of sex on carnitine content of meat is likely be due to the differences in age of the animals.…”
Section: Resultscontrasting
confidence: 86%
“…34 In addition, it was reported that the carnitine content increased with the age of the animal. 33 Hence the contradictory result found in this study compared with previous experiments regarding the effect of sex on carnitine content of meat is likely be due to the differences in age of the animals. However, future studies are required to confirm this phenomenon.…”
Section: Effect Of Sexcontrasting
confidence: 84%
See 2 more Smart Citations
“…The skeletal muscles of male rats had high l -carnitine content compared with those of female rats ( Borum, 1978 ). Abuzaid (2010) found a higher l -carnitine content in beef from male Angus than in that from female Angus.…”
Section: Resultsmentioning
confidence: 77%